2022
DOI: 10.3390/genes13040590
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Circulating Cell-Free DNA in Assessing Microsatellite Instability and Loss of Heterozygosity in Breast Cancer Using Human Identification Approach

Abstract: The diagnostic and prognostic utility of circulating cell-free DNA (cfDNA) in breast cancer (BC) patients was recently reported. Here, we investigated the use of cfDNA to examine microsatellite instability (MSI) and loss of heterozygosity (LOH) for early BC diagnosis. cfDNA and genomic DNA from 41 female BC patients and 40 healthy controls were quantified using NanoDrop spectrophotometry and real-time PCR. The stability of genomic and cfDNA was assessed using a high-resolution AmpFlSTR MiniFiler human identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Another study showed that the incidence of LOH was significantly correlated with lymph node status in terms of the relative concentration of DNA in preoperative serum in patients with breast cancer, in patients with benign breast disease, and in healthy women ( 36 ). In addition, a study of the differences in MSI and LOH between breast cancer and healthy women showed significant differences in some alleles ( 65 ). These collective findings underscore the value of comprehensive ctDNA studies in the early diagnosis of breast cancer.…”
Section: Ctdna and Breast Cancer Diagnosismentioning
confidence: 99%
“…Another study showed that the incidence of LOH was significantly correlated with lymph node status in terms of the relative concentration of DNA in preoperative serum in patients with breast cancer, in patients with benign breast disease, and in healthy women ( 36 ). In addition, a study of the differences in MSI and LOH between breast cancer and healthy women showed significant differences in some alleles ( 65 ). These collective findings underscore the value of comprehensive ctDNA studies in the early diagnosis of breast cancer.…”
Section: Ctdna and Breast Cancer Diagnosismentioning
confidence: 99%
“…Consequently, we have to prepare ourselves more strongly to fight this lethal ailment. Among many approaches, chemotherapy is gaining importance as a way to treat different types of cancers [2][3][4][5][6] but it has been associated with several side effects. The most serious side effects are lymphedema, severe pain, fatigue, loss of appetite, swelling and drainage from the site of surgery, bleeding, infection, and organ dysfunction [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%